2013
DOI: 10.1080/00223131.2013.807999
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of wall lubrication force on liquid velocity in turbulent bubbly two-phase flows

Abstract: Based on the significance of a computational fluid dynamics (CFD) simulation of dispersed two-phase flow systems in many engineering fields, especially in nuclear energy systems, extensive analytical and numerical studies of wall lubrication force for vertical upward turbulent bubbly two-phase flow are presented. An analytical expression of the wall lubrication force considering the effect of liquid velocity is developed and analyzed. A numerical methodology for evaluating the wall lubrication force coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Two different correlations were given for different pipe sizes, which means that the scale-up capability of the coefficients to small or large diameter system was not validated. Nguyen et al (2013b) concluded the effect of the lift coefficient could be negligible at low superficial liquid velocity conditions and a good agreement was obtained at high superficial velocity conditions with the reduced lift coefficient of 0.0066.…”
Section: Investigatorsmentioning
confidence: 62%
See 1 more Smart Citation
“…Two different correlations were given for different pipe sizes, which means that the scale-up capability of the coefficients to small or large diameter system was not validated. Nguyen et al (2013b) concluded the effect of the lift coefficient could be negligible at low superficial liquid velocity conditions and a good agreement was obtained at high superficial velocity conditions with the reduced lift coefficient of 0.0066.…”
Section: Investigatorsmentioning
confidence: 62%
“…In the CFD simulation, Nguyen et al adopted a set of interfacial force models but the effects of the interfacial drag models on the two-phase flow parameter profiles were not discussed. Nguyen et al (2013b) developed an empirical correlation of the coefficients in wall lubrication force model for a fixed combination of the interfacial drag force models. The developed empirical constants in the wall lubrication force, which were nondimensionalized by the lift force coefficient, were in proportional to superficial liquid velocity.…”
Section: Investigatorsmentioning
confidence: 99%
“…This force is called wall lubrication force. Nguyen et al [30] verified that liquid velocity relies on wall lubrication force. Therefore, the model of the wall lubrication force used in this part of the simulation was Tomiyama's equation [31]…”
Section: Wall Lubrication Forcementioning
confidence: 99%
“…As the Frank model has not been confirmed in smaller or larger pipe diameters, a few later models are developed to extend the application range of this model. Nguyen et al 278 later investigated the coefficient in a larger diameter pipe and developed new correlations considering the superficial liquid velocity. Gao et al 276 modified the Frank et al model by considering the device dimension on wall lubrication force.…”
mentioning
confidence: 99%